Factors Affecting Anemia Status in Adolescent Girls - misroh mulianingsih, misroh mulianingsih (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
ABSTRACT According to Riskesdas 2018, the prevalence of anemia in adolescent girls is very high, at 84.5%. Data from the City of Mataram Health Department in 2017 Puskesmas Selaparang the highest prevalence was 50.43%. Based on the Hb level screening conducted by the Selaparang Health Center, the highest number of anemia in SMAN 9 Mataram was 63 students. The impact of anemia in adolescents, namely decreased reproductive health, decreased learning rates, a height that has not been achieved maximally decreased motor development, and inhibited brain intelligence. Anemia during adolescence will be very influential during pregnancy, childbirth, prematurity, and low birth weight. The purpose of this study was to determine the relationship between parents' income factors, maternal education, tea-drinking habits, knowledge, attitudes, iron supplement intake, menstrual conditions, and the incidence of anemia in adolescent girls at SMAN 9 Mataram in 2018. This research is a quantitative study with a cross approach sectional. The sampling technique was nonprobability sampling, namely total sampling and a total sample of 63 people who were identified as anemic in 2018. Data analysis used the chi-square test. Based on the results of statistical analysis, there was a relationship between parents' income (p = 0.004), maternal education (p = 0.000), knowledge (p = 000), consumption of iron supplements (p = 0.008), and menstrual conditions (p = 0.004). ) with the incidence of anemia in adolescent girls at SMAN 9 Mataram in 2018, and there is no relationship between the habit of consuming tea (p = 0.753) and attitudes (0.323) with the incidence of anemia in adolescent girls at Mataram Senior High School in 2018. Based on the research results, suggestions that can be suggested that the Mataram City Health Office collaborate with the Puskesmas in evaluating the program's implementation should immediately follow up. Keywords: Anemia, young women